2016
DOI: 10.1038/cddis.2016.266
|View full text |Cite|
|
Sign up to set email alerts
|

ZIKA virus elicits P53 activation and genotoxic stress in human neural progenitors similar to mutations involved in severe forms of genetic microcephaly and p53

Abstract: Epidemiological evidence from the current outbreak of Zika virus (ZIKV) and recent studies in animal models indicate a strong causal link between ZIKV and microcephaly. ZIKV infection induces cell-cycle arrest and apoptosis in proliferating neural progenitors. However, the mechanisms leading to these phenotypes are still largely obscure. In this report, we explored the possible similarities between transcriptional responses induced by ZIKV in human neural progenitors and those elicited by three different genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 74 publications
2
108
1
1
Order By: Relevance
“…The expression of TACI and BCMA proteins, BAFF and APRIL receptors, have been demonstrated to be critical for the maintenance of ASC and antibody responses (44, 45). RNA-seq data from ZIKV infected neural progenitor cells showed downregulation of TNFRSF13C, another BAFF receptor (46). Considering that ZIKV loads can present a long duration in body fluids and antigen-specific ASCs are still found in low frequencies, it remains to be elucidated whether ZIKV infection also dampens the expression of BAFF receptors in B cells in vivo , impacting the titers of anti-ZIKV antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TACI and BCMA proteins, BAFF and APRIL receptors, have been demonstrated to be critical for the maintenance of ASC and antibody responses (44, 45). RNA-seq data from ZIKV infected neural progenitor cells showed downregulation of TNFRSF13C, another BAFF receptor (46). Considering that ZIKV loads can present a long duration in body fluids and antigen-specific ASCs are still found in low frequencies, it remains to be elucidated whether ZIKV infection also dampens the expression of BAFF receptors in B cells in vivo , impacting the titers of anti-ZIKV antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV infection increases total levels of tumor suppressor protein p53, its nuclear accumulation, and Ser15 phosphorylation (Ghouzzi et al, 2016) and p53 inhibitors block the apoptosis induced by ZIKV in human neural progenitors (Zhang et al, 2016a). Together these findings show that ZIKV interferes with key survival and homeostasis mechanisms, which helps explain the pleiotropic and destructive consequences of infection in cells and tissues.…”
Section: Mechanisms Underlying Zikv Infection and Pathogenesismentioning
confidence: 99%
“…Activation of p53 has also been reported after the infection of iPSC-derived human NPC with a ZIKV strain isolated from French Polynesia (PF13). The activation of p53 was not restricted to NPC expressing high levels of viral antigens (Ghouzzi et al, 2016), suggesting that this might be an early event or an indirect effect of ZIKV infection in neighboring cells. Other cell types, such as microglia, astrocytes, and endothelial cells, can also be infected Lum et al, 2017;Meertens et al, 2017), but it is unknown how the interplay among different cell types contribute to the outcome of microcephaly.…”
Section: Are There Any Differences In the Neurovirulence Of Differentmentioning
confidence: 99%
“…Studies using an Asian strain of ZIKV (FSS13025, isolated in Cambodia) or ZIKV isolated from recent outbreaks in Brazil (Cugola et al, 2016;Souza et al, 2016;Garcez et al, 2017;Sacramento et al, 2017), Puerto Rico (Hanners et al, 2016;Wells et al, 2016) and French Polynesia (Ghouzzi et al, 2016) have shown the ability of the virus to infect and induce apoptosis of human NPC.…”
Section: Zikv Induces Apoptosis Autophagy and Mitotic Abnormalities mentioning
confidence: 99%